2003
DOI: 10.1016/s0887-2333(03)00051-1
|View full text |Cite
|
Sign up to set email alerts
|

Loss of mitochondrial transmembrane potential and caspase-9 activation during apoptosis induced by the novel styryl-lactone goniothalamin in HL-60 leukemia cells

Abstract: Styryl-lactones such as goniothalamin represent a new class of compounds with potential anti-cancer properties. In this study, we investigated the mechanisms of goniothalamin (GTN), a plant styryl-lactone induced apoptosis in human promyelocytic leukemia HL-60 cells. This plant extract resulted in apoptosis in HL-60 cells as assessed by the externalisation of phosphatidylserine. Using the mitochondrial membrane dye (DIOC(6)) in conjunction with flow cytometry, we found that GTN treated HL-60 cells demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
67
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 34 publications
7
67
0
Order By: Relevance
“…Previous study reported that the sequential activation of caspase-9 but not caspase-8 leading to the downstream caspase-3 cleavage was observed in GTN-treated CASMCs (Cononary Artery Smooth Muscle Cells) . It has also been reported that GTN induced apoptosis in HL-60 and Jurkat cells via mitochondrial pathway (Inayat-Hussain et al, 2003;. Thus, this findings suggested that the insignificant role of caspase-8 as an initiator caspase.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Previous study reported that the sequential activation of caspase-9 but not caspase-8 leading to the downstream caspase-3 cleavage was observed in GTN-treated CASMCs (Cononary Artery Smooth Muscle Cells) . It has also been reported that GTN induced apoptosis in HL-60 and Jurkat cells via mitochondrial pathway (Inayat-Hussain et al, 2003;. Thus, this findings suggested that the insignificant role of caspase-8 as an initiator caspase.…”
Section: Discussionsupporting
confidence: 59%
“…This may be contributed to by changes in the cell membrane triggered by the high goniothalamin concentrations, which may increase the uptake of trypan blue dye and the subsequent membrane alteration may have gradually resulted in cell death. Some evidence has indicated that goniothalamin exposure can alter the membrane properties (Inayat-Hussain et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results conducted to other studies investigated the cytotoxic effect of Goniothalamin towards human breast cancer, vascular smooth muscle cells (VSMCs), Jurkat leukemia cells, HL-60 leukemia cells, Chinese hamster ovary (CHO) and hepatoblastoma HepG2 cells (Ali et al, 1997;Pihie et al, 1998;Inayat-Hussain et al, 1999;Inayat-Hussain et al, 2003;Nasir et al, 2004;Chen et al, 2005;Chan et al, 2006;Al-Qubaisi et al, 2011).…”
Section: Discussionmentioning
confidence: 92%
“…However, many cancer cells, such as leukemic HL-60 cells, Jurkat T cells, colon HT29 cells were induced to undergo apoptosis by GTN as well (Alabsi et al, 2012;Inayat-Hussain et al, 2003;InayatHussain et al, 2010;Inayat-Hussain et al, 1999). Even though there are reports of mechanisms of cancer cell apoptosis induced by GTN to be mitochondrial pathway, the cross-link between the extrinsic and intrinsic pathways remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…GTN, a plant styrylpyrone derivative, induces apoptosis in Jurkat T-cells as assessed by the externalization of phosphatidylserine via caspase-3 and -7 activation (Inayat-Hussain et al, 1999). It induces leukemic HL-60 cell apoptosis via the loss of mitochondrial transmembrane potential and caspase-9 activation (Inayat-Hussain et al, 2003). Even though there are several reports of the apoptotic induction of GTN in many cancer cell lines, the involvement of extrinsic pathway remains elusive.…”
Section: Introductionmentioning
confidence: 99%